Maintenance of Fluorescence During Paraffin Embedding of Fluorescent Protein-Labeled Specimens - Zhanmu, Ouyang; Zhao, Peilin; Yang, Yang; Yang, Xiaoquan; Gong, Hui; Li, Xiangning (Frontiers in Neuroscience, 2019)
Paraffin embedding is widely used in microscopic imaging for preparing biological specimens. However, owing to significant fluorescence quenching during the embedding process, it is not compatible with fluorescent-labeling techniques, such as transgenic and viral labeling using green fluorescent protein (GFP). Here we investigated the quenching mechanism and optimized the embedding process to improve the preservation of fluorescence intensity. The results showed that dehydration is the main reason of fluorescence quenching during paraffin embedding, caused by full denaturation of GFP molecules in ethyl alcohol. To evaluate fluorescent and morphological preservation, we modified the embedding process using tertiary butanol (TBA) instead of ethyl alcohol. Fluorescence intensity following TBA dehydration increased 12.08-fold of that observed in the traditional method. We obtained uniform fluorescence maintenance throughout the whole mouse brain, while the continuous apical dendrites, spines, and axon terminals were shown evenly within the cortex, hippocampus, and amygdala. Moreover, we embedded a whole rat brain labeled with AAV in the prelimbic cortex (Prl). With the axon terminals in different areas, such as the caudate putamen, thalamus, and pyramidal tract, the results showed a continuous tract of Prl neurons throughout the whole brain. Meanwhile, this method was suitable to tdTomota labeled samples. These findings indicated this modified embedding method could be compatible with GFP and provides a potential turning point for applications in the fluorescent labeling of samples.